Evaluation of 92 cardiovascular proteins in dried blood spots collected under field‐conditions: Off‐the‐shelf affinity‐based multiplexed assays work well, allowing for simplified sample collection. (15th February 2021) - Broberg, Karin; Svensson, Johanna; Grahn, Karin; Assarsson, Eva; Åberg, Mikael; Selander, Jenny; Enroth, Stefan
Abstract: Workplace‐collected blood spots deposited on filter paper were analysed with multiplexed affinity‐based protein assays and found to be suitable for proteomics analysis. The protein extension assay (PEA) was used to characterize 92 proteins using 1.2 mm punches in repeated samples collected from 20 workers. Overall, 97.8% of the samples and 91.3% of the analysed proteins passed quality control. Both within and between spot correlations using six replicates from the same individual were above 0.99, suggesting that comparable levels are obtained from multiple punches from the same spot and from consecutive spots. Protein levels from dried blood and wet serum from the same individuals were compared and the majority of the analysed proteins were found to be significantly correlated. These results open up for simplified sample collection of blood in field conditions for proteomic analysis, but also highlight that not all proteins can be robustly measured from dried whole blood. Abstract : Dried blood spots (DBS) are an attractive alternative to phlebotomy because of ease of sampling and handling. To better characterize the utility of DBS, paired serum and multiple punches from field‐collected DBS were compared and analyzed in terms of correlation and stability in measurements of protein biomarkers for cardiovascular disorders.